تأثير اللهجة الملايوية على مستوى الكفاءة النطقية في قراءة النص العربي: دراسة تحليلية - Muhammad Ridha bin Ali Huddin (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research investigates Arabic and Malay phonetics, the airstream mechanism (pulmonic egressive) and manner of articulation. This research also examines the ability of Malays to sound like native speakers of Arabic, to identify the difficulties Malays have when pronouncing Arabic letters and words and to identify a solution. Also, this research analysed the Qur'an recitation of two groups in Kedah and Kelantan by using a software called Praat. The researcher finds that the focus on Arabic phonetics and phonology is very low, either in the primary schools or in universities. This problem becomes even more crucial when the researcher finds that there are still many Malays who cannot pronounce Arabic alphabets correctly, especially in Kedah and Kelantan due to the strong dialect. The error in Arabic pronunciation reflects the quality of Qur'an recitation. The researcher also wants to evaluate the level of pronunciation when reading Arabic texts in terms of the accuracy of the pronunciation (airstream mechanism and manner of articulation). The researcher also considers the frequency of Qur'an recitation as the variable that contributes to the dependent variable which is the level of pronunciation when reading Arabic texts. This study conducted a field study in which the researcher took 10 participants from the two states and one native speaker from Palestine as a measure to them. In addition, the researcher interviewed two university lecturers who are experts in the field. The results show that there is definitely an influence of the Kedah dialect on pronunciation competence in reciting the verses containing al-fathah (marked letter), but not the ones without. However, there is an influence of the Kelantan dialect in pronouncing single letters especially nasal letters namely al-Jiim, al-Siin, al-Syiin, al-Ain, al-Ghain, al-Miim and al-Nuun. In spite of this, all participants from both groups are able to pronounce al-Haa'.